Etnobotânica de plantas antimaláricas em comunidades indígenas da região do Alto Rio Negro – Amazonas – Brasil - Kffuri, Carolina Weber [UNESP] (2014)
More than 3.3 million people worldwide are exposed to malaria. The drugs used in combating the disease already show signs of resistance. In Brazil 99% of cases occur in Legal Amazônia. It is an endemic disease in the Upper Negro River considered a sui generis cultural region, where more than 90 % of inhabitants are native speakers of 23 languages, and the forest is preserved and unknown to science. It is the first ethnobotanical work on antimalarial plants in the region. Negotiations for obtaining research permission were intense between 2010 and 2013. And the fieldwork was carried out between September 2011 and July 2012 and September and November 2013, in five indigenous communities . 46 species are used to treat malaria were recorded belonging to 24 botanical families, most native of the Amazon phytogeographical area. Cultural perceptions of the disease were recorded, as well as the name of some plants in the two major languages of the region and a study of fitonímia in Língua Geral Amazônica was made. 14 of the 46 species have scientific studies proving its antimalarial activity and 25 can be considered interesting for future scientific studies. Only five species showed consensus in use. The large number of native species used and cultural perceptions of the participants about the disease demonstrate that there is local knowledge and its application as the need for environmental and cultural protection of these area, and the urgency of programs that promote the local medical culture and assist intercultural understanding.